Effect of bilio-digestíve reflux on the gastric mucosa. - Girardi, Gino; Santandreu, Jorge; de Freitas, Lourdes; Curbelo, Elbio; Siécola, Osvaldo; Esperón, Alejandro; Tellechea, Miguel A; Burghi, Gustavo; Bonaba, Roberto (Cirugía del Uruguay, 1984)
Study of the effects bile and bilio-duodenal-pancreatic secretions on the gastric mucosa of the dog. The investigation is carried out on two series ol 20 animals each, over a period between 7 and 60 days. Upon biopsy, the animals are examined from the clinical and the anatomo-patological point of view. Authors conclude that pure bile produces severe chronic gastritis accompanied with intestinal metaplasia, while the bilio-duodeno-pancreatic fluid produces a milder chronic gastritis, without intestinal metaplasia.